A stiffened plate buckling model for calculating critical stress of distortional buckling of CFS beams. (September 2016) - Zhu, Jue; Li, Long-yuan
Abstract: This paper presents a novel stiffened plate buckling model for describing the distortional buckling of cold-formed steel zed- and channel-section beams when they are bent about their major axis. In the model the compression flange and lip together with the web are treated as a plate with an angle stiffener. By using the classical principle of total potential energy, an analytical expression for the critical buckling stress of the stiffened plate is obtained. In order to validate the present model, finite strip analysis is also carried out for 59 CFS channel-section beams used in the UK market. The comparison of the critical stresses calculated from the present stiffened plate buckling model and those obtained from the finite strip analysis demonstrates that the present model provides an excellent prediction for the critical stress of distortional buckling of CFS section beams. Highlights: A stiffened plated buckling model is developed for describing distortional buckling of CFS beams. Two formulae are derived for calculating critical stresses of distortional buckling for beams with and without lateral restraint. The present stiffened plate model is validated by using finite strip analysis.